Pendampingan Pastoral Konseling Terhadap Orang Tua Yang Mengalami Kemiskinan - Benny Christian Hutabarat; Rencan Carisma Marbun (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
Poverty is a situation where a person is unable to fulfill his life needs in terms of food, clothing, shelter and education. This writing uses a qualitative descriptive design. Qualitative research is research that aims to describe, discover and understand the meaning of data obtained from a number of people who are the research targets of social and humanitarian issues. This research method is a visit, a pastoral conversation, where the companion is present to provide encouragement, motivation, listen to any struggles and problems faced by the counselee and provide social assistance. And in the form of Pastoral Assistance, the aim is to provide Supportive Counseling, namely counseling to strengthen and support each other (1 Thess. 5:11; Heb. 3:13; 10:25).